White lady a novel - Winspear, Jacqueline 1955- (New York, NY Harper, an imprint of HarperCollins Publishers, 2023)
"The White Lady introduces yet another extraordinary heroine from Jacqueline Winspear, creator of the best-selling Maisie Dobbs series. This heart-stopping novel, set in Post WWII Britain in 1947, follows the coming of age and maturity of former wartime operative Elinor White--veteran of two wars, trained killer, protective of her anonymity--when she is drawn back into the world of menace she has been desperate to leave behind. A reluctant ex-spy with demons of her own, Elinor finds herself facing down one of the most dangerous organized crime gangs in London, ultimately exposing corruption from Scotland Yard to the highest levels of government. The private, quiet "Miss White" as Elinor is known, lives in a village in rural Kent, England, and to her fellow villagers seems something of an enigma. Well she might, as Elinor occupies a "grace and favor" property, a rare privilege offered to faithful servants of the Crown for services to the nation. But the residents of Shacklehurst have no way of knowing how dangerous Elinor's war work had been, or that their mysterious neighbor is haunted by her past. It will take Susie, the child of a young farmworker, Jim Mackie and his wife, Rose, to break through Miss White's icy demeanor--but Jim has something in common with Elinor. He, too, is desperate to escape his past. When the powerful Mackie crime family demands a return of their prodigal son for an important job, Elinor assumes the task of protecting her neighbors, especially the bright-eyed Susie. Yet in her quest to uncover the truth behind the family's pursuit of Jim, Elinor unwittingly sets out on a treacherous path--yet it is one that leads to her freedom"--
111394
Keywords: Women spies -- Fiction; Organized crime -- Fiction; Police corruption -- Fiction; Kent (England) -- Fiction; England -- Kent; Detective and mystery fiction; Fiction; Historical fiction; Novels